Task-based needs analysis: Identifying communicative needs for study abroad students in Japan. (February 2019) - Iizuka, Takehiro
Abstract: This study explores the communicative needs of summer study abroad students in Japan. Despite the growing popularity of Task-Based Language Teaching (TBLT), identifying target tasks through needs analysis (NA), which is an integral part of the approach, is often skipped by teaching professionals and curriculum designers, potentially obscuring the benefits TBLT can offer. The present study focuses on this important yet less-explored stage of TBLT. U.S. study abroad students in Japan and their local host families were surveyed through semi-structured interviews and questionnaires (i.e., triangulation by sources and methods). The results revealed the learners' speaking-oriented immediate needs, as well as several important yet problematic tasks. The study also showed some discrepancies in perception of problems around homestay between students and local families due to cultural differences, which may have been solved if learners had been aware of them. The present investigation highlights the importance of NA for curriculum construction, calling for more frequent and systematic implementation of NA in the field.